EFISIENSI PENGELOLAAN MANAJEMEN PARKIR OFFSTREET TERHADAP PENDAPATAN ASLI DAERAH KOTA BANDA ACEH - Zul Bahri; Dedek Ariansyah; Bunyamin Bunyamin (Universitas Teuku Umar, 2022)
The development of the transportation system in Banda Aceh City every year experiences a very significant development. This has an impact on inadequate transportation facilities and infrastructure. This problem urges the Banda Aceh city government, especially agencies related to the Department of Transportation, to be able to overcome problems that arise such as congestion and limited parking space. This study aims to determine the role of the Banda Aceh City Transportation Service, the factors that support and hinder the implementation of electronic off-street parking in Banda Aceh City and the amount of PAD received from the off-street parking sector. The result of this research is that the Banda Aceh City Transportation Service is responsible for offstreet parking management management on Jl. T. Panglima Nyak Makam and the supporting factors are reducing congestion, preventing PAD leakage, making parking management more orderly, while the inhibiting factors are limited parking space, budget and implementation of the non-cash payment system that has not been 100% implemented. The results of data analysis of the average number of two-wheeled vehicles are 550 vehicles per day and four-wheeled vehicles are 213 vehicles. Revenue per day for two-wheeled vehicles Rp. 550,000 and 4-wheeled vehicles Rp. 426,000. If accumulated for 1 year of Rp. 356,240,000 compared to the manual parking system in 2016 of Rp. 32,770,000, the application of this electronic parking system has increased by 987% per year.